Short-Term Perioperative Outcomes and Complications in Chronic Immunosuppressant Users following Total Hip Arthroplasty - Curtis, Gannon L.; Chughtai, Morad; Khlopas, Anton; George, Jaiben; Sodhi, Nipun; Harwin, Steven F.; Bonutti, Peter M.; Barsoum, Wael K.; Higuera, Carlos A.; Mont, Michael A. (The Journal of Hip Surgery, 2017)
As the rate of total hip arthroplasties (THA) being performed continues to increase, orthopaedic surgeons are likely to operate on patients who use systemic immunosuppressants for a variety of ailments. It may be necessary to continue these medications perioperatively, and it has been reported that they may affect post-operative outcomes. The authors proposed the following questions: (1) Are perioperative outcomes (i.e., operative time, lengths-of-stay, and discharge disposition) affected by chronic immunosuppressant use during THA, and (2) does chronic immunosuppressant use increase the rate of complications within 30-days of THA? The American College of Surgeons National Surgical Quality Improvement Program database was used to identify all THAs from 2008 to 2014. Only osteoarthritis diagnoses were included, and any emergency or concurrent surgeries were excluded. The authors identified 64,796 cases that met the inclusion/exclusion criteria. Prior to surgery, 1,900 patients used chronic immunosuppressants, while 62,896 patients did not use immunosuppressants. Lengths-of-stay, operative time, discharge destination, and 30-day complication rates were the measured perioperative outcomes. To determine significant outcome differences between cohorts, univariate analysis was applied. Next, multivariate regression analysis helped determine if immunosuppressant use independently increased the risk for the measured outcomes and complications. Chronic immunosuppressant users were at higher risk of certain adverse perioperative outcomes and short-term complications. Compared with the control group, immunosuppressant users were more likely to be discharged to a non-home facility (odds ratio [OR]: 1.16; 95% confidence interval [CI]: 1.03–1.31). These patients also had greater rates of septic shock (OR: 2.88; 95% CI: 1.08–7.67) and 30-day readmission (OR: 1.37; 95% CI: 1.10–1.70). Chronic immunosuppressant use leads to higher rates of complications and adverse outcomes following THA. Adverse outcomes related to immunosuppressant use included higher rates of non-home discharge. Complications related to immunosuppressant use included septic shock and 30-day readmission.
Keywords: total hip arthroplasty; complications; steroids; immunosuppression